Stratigraphic Sequence and Structural Evolution of the Sana'a Basin - Al-Subbary, Abdulkarim; Al-Kotbah, Ahmed; Abu-Lohom, Naif; Al-Asadi, Abeer (Thamar University Journal of Natural & Applied Sciences, 2023)
The stratigraphic sequence of the Sana'a basin ranges in age from Precambrian to Recent with some periods missing. Lithological outcrops of the Sana'a basin ranging in age from Jurassic to Quaternary, while the subsurface data reveals the occurrences of the Precambrian rocks. Current research discusses the sedimentary and structural evolution of the Sana'a basin and indicates that significant tectonic phases occurred during the Jurassic, Cretaceous, Tertiary and Quaternary periods. Structural effects of these tectonic phases include uplift and subsidence for several times. However, the Sana'a basin formed during the Jurassic time under an inherited and reactivated structural control from the old N-S trend. Field studies indicate that the Sana'a basin was subjected to compression stage during the Paleocene time which resulted in the formation of an anticline with N-S axis, and then at the end of the Paleocene the area is affected by extensional faults to form half grabens such as Wadi Dhahr, and Haddah half grabens.During the Tertiary Sana'a area has been affected by huge of volcanic activities especially in the southern part of the Sana' a basin to form the Yemen Plateau, then the major tectonic trends were reactivated by extensional stage which coincided with the NS - NW and ENE - WSW trend. However, most of these faults and fractures are filled by volcanic dykes of different composition. In Quaternary time another volcanic activity has occurred to form a lot of plugs and cones intruded into the old rock units.